Esl performance in reading motivation and reading comprehension in democratic and authoritarian contexts. - Maryam Habibian (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
In spite of much great research since the last three decades, still there are many essential things about motivation that we need to know. it becomes a mystery because although it exists in everyone but the way of showing if different in terms of degree, time and context. one of the important responsibilities of school administrator is discovering and nurturing motivation between individuals in any educational process. The purpose of the study is to investigate the process of reading motivation and reading Comprehension in relation to both Malaysian higher educational context types namely, Democratic and Authoritarian with learners' gender to find out whether the degree of performance qualitatively vary as educational context and learners variable vary. To this end, three hypotheses were raised,which were tested through lengthy and multi instrumental procedures, Results showed that educational context have significant effect on learner performance. Students out performed in Democratic context in both reading motivation and reading comprehension and the Democratic educational setting gender groups showed highest performance level and the Authoritarian setting groups atood as a lowest performance.